IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PORTOFOLIO UNTUK MENINGKATKAN KUALITAS PROSES DAN HASIL BELAJAR BIOLOGI - &, Neni Hasnunidah (Pendidikan Dasar, 2008)
Abstract; The study aimed at improving students achievement and the quality of process in studying biology at SMP YP Unila in the academic year 2005/2006. Classroom Action Research (CAR) were used as a method of study involved two cycles. The concept of virus was studied in cycle I and monera-protista was studied in cycle II. Parameters used to know improving the quality of process and achievement were test formative score, daily activity score, student homework score, and score of activity in looking for data and information. The results of the study showed that the implementation of portfolio based learning model enhanced the quality process and student achievement from cycle I to cycle II (9,42%). The score of test formative, student homework, daily activity, and  activity in looking for data and information  increase 15,71%; 15,02%; 6,19%; and 2,64%, respectively.